Advancing Women’s Access to Menstrual-Friendly Toilets towards Ending Period Poverty: A Public Health Imperative in the Philippines - Jerico Ogaya; Ryan Guinaran; Catherine Alesna; John Don Opina; Shaila Pilo; Vic Arthur Masliyan; Christian Joseph Ong; Pearl Irish De Paz; Carina Joane Barroso; Rheajane Rosales; Analyn Españo; Don Eliseo III Lucero-Prisno (Recoletos Multidisciplinary Research Journal, 2025)
Menstrual health and hygiene (MHH) remains critically neglected in the Philippines despite its fundamental role in promoting the well-being, dignity, and empowerment of women and girls. This persistent lapse disproportionately impacts the well-being, education, and social mobility of women and girls across the country. Deep-rooted stigma, outdated land-use practices, and a lack of gender-sensitive planning have resulted in fragmented and inconsistent menstrual hygiene infrastructure. While promising initiatives—such as localized policies, educational campaigns, and innovative digital tools like period tracking apps—have begun to surface, these efforts remain isolated, lack scalability, and often face resistance from conservative sectors. This perspective article highlights the urgent need to mainstream MHH within the country’s public health and development frameworks. By institutionalizing gender-sensitive sanitation infrastructure, ensuring privacy and dignity in public spaces, and adopting inclusive tools such as the Menstrual-Friendly Public Toilet (MFPT) Toolkit, the Philippines can begin to dismantle systemic barriers in advancing access to MFPT. Tackling period poverty is an integral step towards building a more equitable and inclusive society for all.